An investigation into sexting of adolescents and adults - Turner-Distin, Ayesha (2020)
The overall aim of this thesis is to deepen the current understanding and knowledge of adolescent and adult sexting behaviour in relation to age, gender, risk, motives, and emotional attachments. In addition, this thesis will explore the legal ramifications that adolescents face for sending and receiving consensual sexts, and the educational implications of this thesis.